From entrepreneurship education to entrepreneurial intention: Mindset, motivation, and prior exposure - Sun, Junhua; Shi, Jingyi; Zhang, Junfeng (Frontiers in Psychology, 2023)
We studied the relationships between entrepreneurship education and entrepreneurial intention among college students, with a focus on the mediating role of an entrepreneurial mindset as well as the moderating roles of learning motivation and prior entrepreneurial exposure. More than 90,000 students from 100 colleges or universities participated in the investigation, the data were subjected to structural equation modeling with Mplus. The results indicated that entrepreneurship education (curriculum attendance and extracurricular activity) significantly enhanced the entrepreneurial mindset of students, which, in turn, strengthened their entrepreneurial intention. In terms of learning, intrinsic motivation positively moderated the relationships between curriculum attendance and entrepreneurial intention/mindset, whereas extrinsic motivation moderated it negatively. Entrepreneurial exposure positively moderated the correlation between extracurricular activity and academic performance. Implications concerning the adjustment of entrepreneurship education to the entrepreneurial climate are discussed.